2013
DOI: 10.1088/0031-9155/58/12/4195
|View full text |Cite
|
Sign up to set email alerts
|

Markerless EPID image guided dynamic multi-leaf collimator tracking for lung tumors

Abstract: Compensation of target motion during the delivery of radiotherapy has the potential to improve treatment accuracy, dose conformity and sparing of healthy tissue. We implement an online image guided therapy system based on soft tissue localization (STiL) of the target from electronic portal images and treatment aperture adaptation with a dynamic multi-leaf collimator (DMLC). The treatment aperture is moved synchronously and in real-time with the tumor during the entire breathing cycle. The system is implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 30 publications
1
62
1
Order By: Relevance
“…A recent method using 1D MRI pencil‐beam navigators to track tissue motion reported accuracy within 1.5 mm in one case of kidney motion (40) . Another real‐time markerless motion tracking method for lung tumor tracking showed a root mean square deviation less than 1 mm (41) . Here we showed that the tracking error was also within 1 mm when using FKM, KHM, and VR‐TPDS methods for segmenting bladder and kidney.…”
Section: Discussionsupporting
confidence: 54%
“…A recent method using 1D MRI pencil‐beam navigators to track tissue motion reported accuracy within 1.5 mm in one case of kidney motion (40) . Another real‐time markerless motion tracking method for lung tumor tracking showed a root mean square deviation less than 1 mm (41) . Here we showed that the tracking error was also within 1 mm when using FKM, KHM, and VR‐TPDS methods for segmenting bladder and kidney.…”
Section: Discussionsupporting
confidence: 54%
“…The electromagnetic transponders provide an internal surrogate of the tumour and their location will affect the accuracy of their surrogate motion. Further research is directed towards markerless MLC tracking that would not require implantation of transponders, a potential source of toxicity, replaced with direct (image-based) tracking [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that both volumetric and planar imaging with the therapy beam will be greatly improved by the target modifications presented here, resulting in improved patient setup and beam's-eye-view in-treatment imaging. 34,[43][44][45] For example, fast and periodic imaging of a lung tumor with a low Z target could be used to update predictive models of respiratory motion, without interruption of the treatment delivery. Previously published imaging work with low Z targets demonstrated a marked improvement in image contrast using a 2.35 MV beam with a carbon target.…”
Section: Discussionmentioning
confidence: 99%